Synthesis and structure of the extended phosphazane ligand [(1, 4-C6H4){N(μ-PNtBu)2NtBu}2]4−. Issue 5 (9th December 2015) - Sevilla, Raquel; Less, Robert J.; García-Rodríguez, Raúl; Bond, Andrew D.; Wright, Dominic S.
Abstract : Reaction of (1, 4-C6 H4 )[N(PCl2 )2 ]2 with t BuNH2 in the presence of Et3 N gives the bridged phosph(iii )azane (1, 4-C6 H4 )[N(μ-PNH t Bu)2 N t Bu]2 (1 H4 ), which can be deprotonated to give the tetraanion (1, 4-C6 H4 )[N(μ-PN t Bu)2 N t Bu]2 4− (1 4− ). The latter represents a new type of phosphazane ligand. Abstract : The reaction of the phenylene-bridged precursor (1, 4-C6 H4 )[N(PCl2 )2 ]2 with t BuNH2 in the presence of Et3 N gives the new ligand precursor (1, 4-C6 H4 )[N(μ-N t Bu)2 (PNH t Bu)2 ]2, deprotonation of which with Bu2 Mg gives the novel tetraanion [(1, 4-C6 H4 ){N(μ-N t Bu)2 (PN t Bu)2 }2 ] 4− .